2017
DOI: 10.3389/fphar.2017.00814
|View full text |Cite
|
Sign up to set email alerts
|

LSD Increases Primary Process Thinking via Serotonin 2A Receptor Activation

Abstract: Rationale: Stimulation of serotonin 2A (5-HT2A) receptors by lysergic acid diethylamide (LSD) and related compounds such as psilocybin has previously been shown to increase primary process thinking – an ontologically and evolutionary early, implicit, associative, and automatic mode of thinking which is typically occurring during altered states of consciousness such as dreaming. However, it is still largely unknown whether LSD induces primary process thinking under placebo-controlled, standardized experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 54 publications
4
83
1
Order By: Relevance
“…As previously mentioned, early studies with mescaline and LSD reported depersonalization-like effects which occasionally involved a loss of bodily awareness (Guttmann and Maclay, 1937 ; Savage, 1955 ; Von Mering et al, 1955 ; Sedman and Kenna, 1964 ). In the psychometrically validated 5D-OAV questionnaire commonly used to assess the subjective experience of altered states of consciousness (Studerus et al, 2010 ), healthy participants score rather high on the “disembodiment” factor, which includes the item “it seemed to me as if I did not have a body anymore,” after administration of psilocybin (Kometer et al, 2012 ; Bernasconi et al, 2014 ; Preller et al, 2016 ; Pokorny et al, 2017 ) and LSD (Schmid et al, 2015 ; Carhart-Harris et al, 2016a , b ; Kraehenmann et al, 2017 ; Liechti et al, 2017 ; Preller et al, 2017b ). The strength of the subjective effects of LSD (as measured by the mean score on the 5D-ASC questionnaire) was found to correlate with the magnitude of increase in functional connectivity in a somatomotor network including the primary motor and sensorimotor cortices, the caudal premotor cortex and the superior parietal lobule (Preller et al, 2017a ).…”
Section: Alterations Of Self-consciousness Induced By Meditation and mentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, early studies with mescaline and LSD reported depersonalization-like effects which occasionally involved a loss of bodily awareness (Guttmann and Maclay, 1937 ; Savage, 1955 ; Von Mering et al, 1955 ; Sedman and Kenna, 1964 ). In the psychometrically validated 5D-OAV questionnaire commonly used to assess the subjective experience of altered states of consciousness (Studerus et al, 2010 ), healthy participants score rather high on the “disembodiment” factor, which includes the item “it seemed to me as if I did not have a body anymore,” after administration of psilocybin (Kometer et al, 2012 ; Bernasconi et al, 2014 ; Preller et al, 2016 ; Pokorny et al, 2017 ) and LSD (Schmid et al, 2015 ; Carhart-Harris et al, 2016a , b ; Kraehenmann et al, 2017 ; Liechti et al, 2017 ; Preller et al, 2017b ). The strength of the subjective effects of LSD (as measured by the mean score on the 5D-ASC questionnaire) was found to correlate with the magnitude of increase in functional connectivity in a somatomotor network including the primary motor and sensorimotor cortices, the caudal premotor cortex and the superior parietal lobule (Preller et al, 2017a ).…”
Section: Alterations Of Self-consciousness Induced By Meditation and mentioning
confidence: 99%
“…Likewise, there is converging evidence from subjective reports that psychedelic drugs can induce a loss of spatial self-location, associated to loss of boundary between self and world and a feeling of unity with everything (Millière, 2017 ): “I felt myself mold into the world around me…,” “My mind started to blend with everything” (R.M., unpublished data from online survey). On the psychometrically-validated 5D-ASC questionnaire, subjects score high on the factor related to “experience of unity” after administration of LSD (Schmid et al, 2015 ; Carhart-Harris et al, 2016a , b ; Kraehenmann et al, 2017 ; Liechti et al, 2017 ; Preller et al, 2017b ) and to a slightly lesser extent psilocybin (Kometer et al, 2012 ; Bernasconi et al, 2014 ; Preller et al, 2016 ; Pokorny et al, 2017 ). This factor includes the items “it seemed to me that my environment and I were one” and “everything seemed to unify into oneness”.…”
Section: Alterations Of Self-consciousness Induced By Meditation and mentioning
confidence: 99%
“…The study was approved by the Ethics Committee of the Department of Public Health of the Canton of Zurich, Switzerland, and the use of LSD was authorized by the Swiss Federal Office for Public Health, Department of Pharmacology and Narcotics, Berne, Switzerland. The current data were collected as part of a larger study (Kraehenmann et al, 2017;Preller et al, 2017Preller et al, , 2018b and the study was registered at clinicaltrials.gov (NCT02451072).…”
Section: Participantsmentioning
confidence: 99%
“…i) There are also reports that 5-HT 2A receptor partial agonism leads to a decreased inner functional connectivity among large-scale brain networks along with an increased inter functional connectivity among the same large-scale brain networks (Kraehenmann et al, 2017a;Kraehenmann et al, 2017b;Müller, Dolder, Schmidt, Liechti, & Borgwardt, 2018;Nichols, 2016, p. 273;Northoff et al, 2006, p. 450;Palhano-Fontes et al, 2015). All psychedelic drugs act as 5-HT 2A receptor partial agonists (Aghajanian & Marek, 1999).…”
Section: Notesmentioning
confidence: 99%